After JCPOA: American grand strategy toward Iran. Issue 1 (1st January 2018) - Wolf, Albert B.
ABSTRACT: If grand strategy is a state's theory of how to produce security for itself, what should the U.S. grand strategy be toward Iran? This is an important question that has only grown since the Trump administration announced it would not recertify Iran under the Joint Comprehensive Plan of Action (JCPOA). This article lays out four options: rollback, offshore balancing, retrenchment, and engagement. Each strategy has its merits as well as its drawbacks.